Numerical investigation changing airflow direction and incoming particle size to reduce residence time in spray dryer - Carles, Henry; Yohana, Eflita; Djaeni, Mohamad; Tauviqirrahman, Mohammad; Bahar, Shofwan; Dharmawan, Eka; Choi, Kwang- Hwan (Edelweiss Applied Science and Technology, 2025)
Spray drying is appropriate for the desiccation of pharmaceutical and alimentary items. Numerical studies with computational fluid dynamics (CFD) on spray dryers can estimate results comparable to experimental methods, so they are widely used in spray dryer research. This numerical simulation aims to examine the correlation between alterations in the input direction from co-current to mixed flow, with differences in temperature and droplet size, and their impact on the residence duration of particles inside the drying chamber, using the k-ω SST turbulence model to simulate the flow, and the standard k-ε to predict particles. In mixed flow, small-diameter droplets (10 and 30 μm) have a longer particle residence time (9.4 and 4.4 seconds) than in co-current flow; on the other hand, it becomes faster (≤1.2 seconds) for droplet diameters ≥50 μm. Spraying droplets in a mixed flow spray dryer will reduce the residence time of particles relative to co-current flow; larger droplet diameters result in shorter residence times.